Une critique du processus d’informationnalisation du système de santé français - Marius André TINE (Tic & Société)
In the healthcare domain, the term “informationalization” is preferred to “information society” or “digital revolution”, because it reflects better the ongoing evolution of the French healthcare system, an evolution which is not aslinear as the official discourse suggests. Official views are based on very short term perspectives, which take into account neither the complexity of socio-organizational and technical changes, nor the disorder in the actual communication that comes with the introduction of new techniques for the day to day delivery of healthcare. In oncology, for example, the devices that are meant to collect, transmit, and exchange clinical information between the oncologist and organ specialists are rarely used. We demonstrate how some important constraints, which may be clinico-organizational, socio-professional or technical, have to be considered before some information and communication techniques can be applied in cancer treatments.